Optimum integration of concentrating solar technologies in a real coal-fired power plant for fuel saving. (15th December 2018) - Rech, Sergio; Lazzaretto, Andrea; Grigolon, Enrico
Highlights: The hybrid system efficiency strongly depends on integration point and solar share. The best design option consists in the by-pass of the highest-pressure preheaters. Maximum hybrid system thermal efficiency (41.31%) is obtained at 7.63% solar share. A solar field area of ∼0.3 km 2 can save 15.4 Mt of coal per year. Larger areas result in higher fuel savings but lower efficiency. Abstract: The integration of Concentrating Solar Power (CSP) technology in large scale fossil-fuelled power plant is one of the best options to promote the necessary transition to a totally renewable electric system starting from the present system. This work provides a complete overview of the possible integration of CSP systems into a real 320 MW coal-fired steam power plant aimed at fuel saving. To this end, detailed off-design models of the existing steam power plant are first built and validated using experimental data measured on the field. Design and off-design models of solar section are then added considering several placement points. Unlike most of the literature, all technical constraints associated with maximum and minimum load of the existing components are also taken into account. The most efficient integration points proposed in the literature plus four new ones are considered in combination with parabolic trough collectors, linear Fresnel collectors or solar towers, for a total of twenty-two different design options. The best integration point results to be in the high-pressure preheater/s: (i) the highest hybrid thermal efficiency (42.67%) is obtained using parabolic trough/molten salt collectors to generate additional high-pressure steam from the drainage water of the last two parallel preheaters (HPH3), (ii) similar thermal efficiencies are achieved in a wide range of solar share (up to 9.1%) by including parabolic through/thermal oil collectors to heat part of the feedwater stream of HPH3 and (iii) 15, 400 tons per year of coal can be saved when the solar field area is approximately four times as much the area of the existing coal storage area.